Essentials of modeling and analytics : retail risk management and asset protection - Speights, David B.; Downs, Daniel M.; Raz, Adi (New York, NY : Routledge, 2017)
"Essentials of Modeling and Analytics illustrates how and why analytics can be used effectively by loss prevention staff. The book offers an in-depth overview of analytics, first illustrating how analytics are used to solve business problems, then exploring the tools and training that staff will need in order to engage solutions. The text also covers big data analytical tools and discusses if and when they are right for retail loss prevention professionals, and illustrates how to use analytics to test the effectiveness of loss prevention initiatives. Ideal for loss prevention personnel on all levels, this book can also be used for loss prevention analytics courses."--Provided by publisher.
Introduction -- Criminology theory and crime prevention -- Retail theft and security -- Basic statistical analysis -- Graphical representation -- Inferential statistics and hypothesis testing -- Common statistical hypothesis tests -- Testing and deploying loss prevention programs -- Introduction to modeling -- Linear regression -- Logistic regression -- Advanced techniques and machine learning models -- Integrating analytics into loss prevention teams -- Conclusion.
Includes bibliographical references.
Keywords: Retail trade -- Security measures; Retail trade -- Risk management; Retail trade -- Statistical methods; Theft -- Prevention